The Painter's Daughter - Klassen, Julie 1964- (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2015)
"In 1815, a painter's daughter on the north Devon coast agrees to marry a stranger to avoid scandal, but her choice is complicated by the return of a former lover and a growing affection for the husband she barely knows."--
Keywords: Man-woman relationships -- Fiction; Triangles (Interpersonal relations) -- Fiction; Regency fiction; Love stories; Christian fiction